Dampak Digitalisasi terhadap Distorsi Pemaknaan Tafsir Ayat Jihad di Kalangan Masyarakat Awam - Agami, Siroj Mentari; Ahmad Nurrohim (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The development of digital technology has brought convenience in accessing religious information, including interpretations of the Qur'an. However, this convenience also presents serious challenges, particularly regarding the potential distortion of the meaning of jihad verses by the general public. Jihad verses have become a primary focus because they are often misunderstood and misused in contexts of violence or extremism, even though these verses possess complex historical backgrounds, conditions, and contexts. When such verses are quoted indiscriminately on digital platforms without adequate explanation, they can lead to serious social and ideological consequences. This study aims to examine the impact of digitalization on the interpretation of jihad verses, focusing on the forms of distortion, causal factors, and the resulting social impacts. Using a descriptive qualitative approach based on literature review and digital content observation, this research finds that jihad verses are frequently cited in a partial and literal manner, without regard to their historical context (asbāb al-nuzūl) or authoritative exegesis. The main contributing factors are low levels of digital religious literacy and the dominance of social media algorithms. This distortion fosters narrow fanaticism, potential radicalization, social polarization, and a negative image of Islam. Strengthening digital religious literacy and reinforcing the role of scholars in the digital da'wah ecosystem are necessary solutions.